The deleterious effects of CDK4/6 inhibition on renal recovery post-acute kidney injury - Shanshan Zhou; Rouzhang Peng; Yanting Shen; Liuwei Huang; Suying Han; Jun Wang; Jie Guo (Scientific Reports)
Abstract Acute kidney injury (AKI) is a common clinical problem, and patients who survive AKI have a high risk of chronic kidney disease (CKD). The acute protective effects of Cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors in AKI have been examined, there is still relatively little known regarding the impact of acute CDK4/6 inhibition on the chronic sequence of AKI. Therefore, we utilized the CDK4/6 inhibitor Palbociclib to examine the long-term effects of CDK4/6 inhibition in a rodent model of ischemic AKI. Palbociclib (Palb) was administered during the acute stage or post the acute stage of AKI and mice were sacrificed 21 days post injury. We found that Palb could cause renal senescence and renal fibrosis. Furthermore, dasatinib (D) plus quercetin (Q) were used to eliminate senescent cells in ischemic AKI murine model and Palb was administered post the treatment of D + Q. We found that Palb could reverse the senolytic and antifibrotic effects induced by D + Q, which indicates that the profibrotic effect of Palb could be ascribed to its pro-senescent effects. Our results demonstrate that CDK4/6 inhibitors treatment might be deleterious on the chronic sequence of AKI.